SPECTROPHOTOMETRIC DETERMINATION OF ACETYLCYSTEINE IN PHARMACEUTICAL FORMULATIONS USING 2,3-DICHLORO-1,4-NAPTHOQUINONE - A. O. Donchenko; S. O. Vasyuk; K. P. Portna (Zaporozhye State Medical University, 2015)
The aim of research was the development and validation ofspectrophotometric method foracetylcysteine assay in pharmaceutical formulations.Тhe proposed method is based on the reaction with 2,3-dichloro-1,4-naphthoquinone and the formation of colored products that exhibit absorption maxima at 425 nm. Introduction Many analytical methods have been published for acetylcysteine assay in pharmaceutical formulations as high-performance liquid chromatography (HPLC), fluorimetry and chemiluminescence. Some of these methods are time consuming or require expensive equipment. Other published methods suffer from lack of selectivity and sensitivity. Spectrophotometry is the most widely used technique in pharmaceutical analysis because it is simple, economic, and easily available to most quality control laboratories. In the present work, we propose a simple and accurate spectrophotometric method for acetylcysteine assay in pharmaceutical formulations. Materials and Methods Reagents: Reference standard acetylcysteinesubstance; 2,3-dichloro-1,4-naphthoquinone. All chemicals and solvents were of analytical grade. DMFA was used as a solvent. Pharmaceutical preparations:powder for oral solution «ACC 200» 200 mgseries number50026151 (Salutas Pharma CmbH, Germany); effervescent tablets «Fluimucil» 600 mg (Zambon S.P.A., Italy) and «ACC LONG» 600 mg (Salutas Pharma CmbH, Germany) series numbers 321284 and DH2740; solution for injections «Fluimucil» 100 mg/ml (Zambon S.P.A., Italy)series number28002492. Solutions: Acetylcysteine stock solution (0,16%); DMFAsolution of 2,3-dichloro-1,4-naphthoquinone (4%). Equipment Analytical balance (ABT-120-5DM); UV-VIS spectrophotometer (Specord 200); water bath (MemmertWNB 7-45);quartz cells. Results Acetylcysteine was determined using a spectrophotometric method based on the reaction with 2,3-dichloro-1,4-naphthoquinone to form yellow colored reaction products with absorption maxima at 425 nm. The effect of reaction time and temperature was studied. It was found that the reaction requires heating at 95°С for 10 min. The proposed method is valid according to the validation requirements of Ukrainian Pharmacopeia. The following parameters were considered: range of application, linearity, accuracy, robustness, precision of the results. Conclusion The proposed spectrophotometric method for quantitative determination of acetylcysteine in pharmaceutical formulations was found to be simple, precise, accurate, linear, robust and rugged during validation. Further this method can be recommended for routine quantitative determination of the studied drugs in quality control laboratories.